Direito à saúde da pessoa idosa vivendo com HIV/AIDS: desafios e possibilidades no âmbito do Sistema Único de Saúde (SUS) - SANTOS, Adan Holiday Damasceno (2020)
The purpose of this present monograph is to analyze if there is or not and what are violations of older people’s rights to health living with HIV / AIDS in the Unified Health System (UHS). Firstly, we sought to highlight data on the elderly in Brazil and their protective legal framework. Then we discuss about the right to health in Brazil and its nuances, such as HIV / AIDS and the importance of UHS to combat the epidemic in the country. Finally, we analyze what are the existing legal violations in this situation and discuss the perspectives and possibilities of treatment given to the elderly living with HIV / AIDS in the UHS scenery. In conclusion, if there is a violation of the right to health of the elderly that becomes hyper vulnerable, even more because of prejudice and stigma imposed by society that causes legislative, legal or public policy failures, subsisting a distance between the protection system of the elderly and the person living with HIV in relation to what is actually practiced. Therefore, a methodology used was a bibliographic research and a monographic procedure, using the deductive method.